(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Preeclampsia is a prevalent pregnancy complication. It is linked to a hyper coagulable condition that raises the risk of both Disseminated Intravascular Coagulation (DIC) and thromboembolism. Patients with preeclampsia have shown changes in their coagulation indices, specifically in D-dimer levels. These changes have been proposed as a very sensitive indicator for identifying abnormal hyper coagulopathy. The objective of this study was to determine the plasma D-dimer level in preeclampsia compared to normal pregnancies and to observe any variations in relation to the severity of the condition. Materials and method: This study was done at the Department of Biochemistry and the Department of Obstetrics and Gynaecology at Chittagong Medical College (CMC) and Chittagong Medical College Hospital (CMCH) respectively. It was an observational study that analyzed data from a single point in time. The key factors were examined in this study included age, BMI, gestation period, blood pressure, and urine protein level. Results: Plasma D-dimer level was higher in severe preeclampsia (1.646 ± 1.120) mg/ml as compared to mild preeclampsia (1.024 ± 0.488) mg/ml and normotensive pregnant (0.611 ± 0.141) mg/ml. The D-dimer was significantly correlated with gestational age. There was a significant mean difference in D-dimer level between preeclampsia and normal pregnancy. D-dimer level of 0.668 mg/ml, the sensitivity is 80% and the specificity is 76% for predicting pre-eclampsia. There was also a significant association of D-dimer with preeclampsia. Conclusion: Preeclampsia is correlated with elevated Ddimer levels in comparison to pregnancies that are considered normal. Plasma D-dimer levels exhibited a positive correlation with the severity of preeclampsia. JCMCTA 2024 ; 35 (2) : 82-86